Challenges and Opportunities in E-Learning Implementation: Lesson from the Past, Principles for the Future - Ima Fitriyah; Fitriatul Masitoh; Khoiruddin Yanuar Syam (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2022)
The corona virus that we've been dealing with since December 2019 resulted in unexpected emergency online instruction. Schools and universities were shuttered, face-to-face teaching and learning activities were suspended, and an emergency online teaching policy was implemented. Consequently, the purpose of this study was to identify the strengths, weaknesses, challenges, and opportunities of EFL lecturers' implementation of E-learning in EFL online classes during the Covid-19 Pandemic. A questionnaire with open-ended questions was used to collect the data. As a result of E-learning implementation, EFL instructors have become more familiar with CALL, according to the study's findings. Considered to be the drawbacks of the E-learning implementation were an unstable internet connection, a lack of direct interaction between lecturers and students, and the inability of EFL teachers to control their students. In addition, EFL instructors were required to oversee, supervise, and direct the entire assessment procedure. On the other side, English online instruction through E-learning generated chances for EFL lecturers, such as supplying more creative media or making their own instructional video.